Pendekatan Metode Extreme Programming untuk Pengembangan Sistem Informasi Manajemen Surat Menyurat pada LPIK STIKI - Sarasvananda, Ida Bagus Gede; Wiguna, I Gede Komang Arya Ganda; Styawati, Styawati (Teknik Informatika Universitas Pamulang, 2021)
In its application, the administrative system at LPIK STIKI still uses conventional methods or has not used the system. There are several obstacles when using the conventional method, namely, letter archiving that is less than optimal, it is still difficult when searching for letters because archiving is not optimal, and generating / making letters is still manual. So to facilitate the administration of correspondence in LPIK STIKI, it is deemed necessary to create a correspondence management administration system. The method used to build a correspondence information system is the Extreme Programming (XP) method. The XP method was chosen because it can build a system in a short time and the demands or business processes of system stakeholders that often change. From the results of research that has been carried out the system built can run as expected by the user, this is evidenced by the results of testing with the black box testing method. The Extreme Programming method approach used by researchers in building the system really helps speed up system development and is proven to be efficient.